The appropriation of privacy: Policies and practices of everyday technology use - Quinn, Kelly; Zimmer, Michael; Fernback, Jan; Baasanjav, Undrah; Marwick, Alice (AoIR Selected Papers of Internet Research, 2013)
Privacy is a complex concept involving dimensions of access and control of shared information, expectations of intended audience, and appreciation of the context in which a communication takes place. As new technologies are introduced and become ubiquitous, they intersect with influences of culture and experience to influence and appropriate privacy’s interpretation and meaning. This panel will explore how conceptions of privacy are shaped and understood by examining the implications that everyday technologies, and the policies and practices embodied therein, hold for the realization of privacy goals. Culture, mobility and utility of new media forms challenge the conception and construction of privacy in these multiple contexts, and these in turn seize and shape our sociability and interactions with others. Intensely cultural, conceptions of privacy highlight the dialectical tensions between public/private and individual/community. Cultural conceptions of privacy inform, are reproduced and embodied in societal norms and political frameworks, and not only impact the individual in physical ways, but also as the body is digitized in communicative acts. Our first presenter will present findings of how mass media in China reproduce the ideological individual/community tensions that surface through the use of human flesh search engines, and how this is embodied in policy and political frameworks. Without clear privacy laws, the Chinese state may easily appropriate the concept of privacy away from the legal terrain of information control or human dignity and toward individual selfishness and shame. Our second presenter will introduce the emerging infrastructures of augmented mobility technologies, and critically interrogate their impact on conceptions – and expectations – of privacy in our infosphere. Emerging augmented mobility platforms are wearable devices that promise to provide new ways of conceiving of our world through the layering of locational information and real-time informational objects onto a physical environment. Location-aware mobile Internet applications provide new layers of information to aid in navigation, decision-making, and social interactions. But they also require widespread tracking, collecting, and aggregating of users’ precise locations, and the sharing of that locational data with third parties, creating the potential for panoptical surveillance and a reengineering of reality that carries ontological consequences. The contextual nature of privacy reinforces an understanding that disclosure contexts and intended audiences are meaningful and relevant. Traditional mechanisms for privacy regulation are challenged by the characteristics of social media, as disclosure is more permanent, sharable and searchable. As these technologies become more ubiquitous and approach near-invisibility in everyday life, understanding the tension between their use and privacy regulation processes becomes more critical. Our third presenter will explore how the utility of social media forms relates to privacy enactment by examining the perceived privacy/sociability trade off. By examining the intersection of sociability and privacy practices among social media users at varying ages we are provided insight into how the utility of these media challenges the conception and understanding of privacy in everyday life. Finally, our fourth presenter will examine the complicated relationship between anonymity and privacy by undertaking a legal and policy analysis of ‘doxxing,’ or public shaming. Recently, in response to online sexist and misogynist speech acts, there has been a series of compromises to online anonymity intended to make an offending individual accountable for their actions. But while public shaming may seem to be an effective solution to those who engage in sexist or racist speech acts, it can just as easily be used to further hateful attitudes towards marginalized groups. This presentation will demonstrate how regulating hate speech may not only hold the possibility for negative consequences for online privacy, but also for desired speech such as activism and protest. By examining privacy and privacy goals through the complex and varied perspectives of technological contexts, practices, and policies, this panel attempts to contribute to our understandings of how privacy is enacted, understood and potentially appropriated in everyday contexts. In doing so, we hope to enhance and refine our understanding of privacy as a desirable and valued outcome.